2009
DOI: 10.1089/neu.2008.0829
|View full text |Cite
|
Sign up to set email alerts
|

Swim Training Initiated Acutely after Spinal Cord Injury Is Ineffective and Induces Extravasation In and Around the Epicenter

Abstract: Activity-based rehabilitation is a promising strategy for improving functional recovery following spinal cord injury (SCI). While results from both clinical and animal studies have shown that a variety of approaches can be effective, debate still exists regarding the optimal post-injury period to apply rehabilitation. We recently demonstrated that rats with moderately severe thoracic contusive SCI can be re-trained to swim when training is initiated 2 weeks after injury and that swim training had no effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 43 publications
1
26
0
2
Order By: Relevance
“…Although different strategies of rehabilitation, such as swimming, bicycling, exercise via wheel running and TT have been applied in experimental models of TSCI with the aim to improve locomotion, not all of them have had a significant effect on functional recovery. Some authors showed no improvement in functional recovery assessed with the BBB scale using swimming as rehabilitation therapy, and compared with untrained animals with a TSCI by contusion since it has been proved that swimming induces extravasation in and around the site of injury [42]. Bicycling has been shown to help prevent muscle atrophy and restore the frequency-dependent depression of the H-reflex to the level of that of intact animals but without significant effects on the functional recovery in rats with spinal cord transection [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Although different strategies of rehabilitation, such as swimming, bicycling, exercise via wheel running and TT have been applied in experimental models of TSCI with the aim to improve locomotion, not all of them have had a significant effect on functional recovery. Some authors showed no improvement in functional recovery assessed with the BBB scale using swimming as rehabilitation therapy, and compared with untrained animals with a TSCI by contusion since it has been proved that swimming induces extravasation in and around the site of injury [42]. Bicycling has been shown to help prevent muscle atrophy and restore the frequency-dependent depression of the H-reflex to the level of that of intact animals but without significant effects on the functional recovery in rats with spinal cord transection [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…This sensory feedback is thought to be important for weight support during training (Edgerton et al, 2004). Indeed, in this review swimming training, which lacks the limbloading phase, was beneficial only when at least cutaneous feedback was provided (i.e., by inverted centrifuge tubes; Kuerzi et al, 2010;Smith et al, 2009Smith et al, , 2006.…”
Section: Exercise Training After Spinal Cord Injurymentioning
confidence: 95%
“…Blinded outcome measures were undertaken in 29% of complete and 54% of incomplete SCI studies (Carvalho et al, 2008;Engesser-Cesar et al, 2007;Erschbamer et al, 2006;Foret et al, 2010;Fouad et al, 2000;Ichiyama et al, 2009;Kubasak et al, 2008;Kuerzi et al, 2010;Lankhorst et al, 2001;Maier et al, 2009;Multon et al, 2003;Oh et al, 2009;Park et al, 2010;Singh et al, 2011;Smith et al, 2006;Tillakaratne et al, 2010;Timoszyk et al, 2005, Zhang et al, 2007. Histological analysis to confirm the extent of the lesion were performed in 76% of complete, but only 46% of incomplete SCI studies (Barriere et al, 2008;Boyce et al, 2007 Kuerzi et al, 2010;Lankhorst et al, 2001;Lee et al, 2010;Liu et al, 2008;Lovely et al, 1986;Maier et al, 2009;Moshonkina et al, 2002Moshonkina et al, , 2004Multon et al, 2003;Nothias et al, 2005;Park et al, 2010;Petruska et al, 2007;Singh et al, 2011;Smith et al, 1982Smith et al, ,2009Smith et al, ,2006Tillakaratne et al, 2010;Ung et al, 2010;Zhang et al, 2007). The three studies (7%; …”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
See 2 more Smart Citations